Perancangan Sistem Informasi Faktur Penjualan pada toko Sari Agung Semarang - Rozaq Isnaini Nugraha; Supriyanto Supriyanto; Sigit Sugiharto (Pixel :Jurnal Ilmiah Komputer Grafis, 2024)
Effective sales transaction management is very important for retail businesses. This research aims to develop a comprehensive sales invoice information system at the Sari Agung Semarang store to improve the efficiency and accuracy of the sales process. The system is designed to simplify invoicing, maintain accurate inventory records, and provide complete sales reporting capabilities. This research involved analysis of current sales processes, system design with a user-friendly interface, and integration with existing accounting and inventory management software. Implementation of this system is expected to increase customer satisfaction, reduce the risk of errors, and provide valuable insights to support better decision making.